Assessment of Water Quality of Shatt Al-Basrah Canal using Water Pollution Index - A. Hassan, Ayman; S. Dawood, Ammar; J. AL-Mansori, Nassrin (International Journal of Engineering and Technology, 2018)
This study evaluates the water quality for the Canal of Shatt Al-Basrah, located in Basrah province, Iraq. The Shatt Al-Basrah Canal used to connect the waterway from Al-Hammar marshes in the north of Basrah province, to Khor Al-Zubair port in the south of the province. Nine physicochemical water quality parameters have been measured and analyzed for calculating the water pollution index (WPI) in the Canal. These parameters, which were used in developing the WPI, included: Potential of Hydrogen (pH), Nitrate (NO3-), Calcium (Ca2+), Total Alkalinity (TA.), Electrical Conductivity (EC), Sodium (Na+), Total Dissolved Solids (TDS), Sulfate (SO42-), Phosphate (PO43-), Dissolved Oxygen (DO), Total Hardness (TH), Chloride (Cl-), Magnesium (Mg2+), and Potassium (K+). The aim of this paper is to analyze and assess the water pollution of the Shatt Al-Basrah Canal in the year 2014, making use of the WPI method.Â The annual WPI mean value during the study period was more than the safe value; therefore, the water quality of the Canal ranged from impure (type V) to the heavily impure (type VI) and hence definitely regarded as unsuitable for drinking uses. Consequently, there is a need that is immediate to take some measures to stop the pollution and enhance the water quality of the Canalas a component that is integral tothe environment in Basrah province. In Basrahprovince, the disposal of wastewater in the Shatt Al-Basrah Canal is big maintenance difficulty of the Canal water quality.Â Â